Net Interest Margins of Banks in India. (May 2019) - Barik, S. S.; Raje, Nishita
Net interest margin (NIM) is the raison d'être of banking. It is an important measure of efficacy of the banking sector. At the system level, it is indicative of the cost of financial intermediation, health of the banking sector and its pricing power. In recent years, the Indian banking sector has experienced a major metamorphosis, with increasing competition and changing norms of liquidity, income recognition and capital. The end of regulatory forbearance and asset quality review (AQR) unearthed significant non-performing assets. This article traces the influence of various factors on the NIM, using bank-level data for 42 Indian banks over 25 quarters from March 2011 to March 2017. The study employs a dynamic panel generalised method of moments (GMM) framework to trace the impact of three distinct set of factors in setting banks' NIMs: bank-level factors (like the share of low interest-bearing deposits held, the extent of gross non-performing assets [GNPAs], the capital-to-risk weighted assets ratio [CRAR], size of the loan book, operating costs and lending rates); system-level factors such as the monetary policy rate, credit growth and yields on government securities and macro-variables such as GDP growth and inflation. The results indicate that the main determinants of NIMs are banks' CRAR levels, the proportion of current account and savings account deposits (CASA) to total deposits, operating costs and size of the loan book. Macro-factors like the growth of the economy and repo rate have a positive influence on the NIM. JEL Classification: C23, E43, G21